2002
DOI: 10.1046/j.1365-313x.2002.01327.x
|View full text |Cite
|
Sign up to set email alerts
|

Conformational features of crystal‐surface cellulose from higher plants

Abstract: SummaryNative cellulose in higher plants forms crystalline ®brils a few nm across, with a substantial fraction of their glucan chains at the surface. The accepted crystal structures feature a¯at-ribbon 2 1 helical chain conformation with every glucose residue locked to the next by hydrogen bonds from O-3¢ to O-5 and from O-2 to O-6¢. Using solid-state NMR spectroscopy we show that the surface chains have a different C-6 conformation so that O-6 is not in the correct position for the hydrogen bond from O-2. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
136
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 157 publications
(146 citation statements)
references
References 59 publications
9
136
1
Order By: Relevance
“…Almost all the cellulose chains were at least moderately well oriented, as shown by both WAXS and polarized FTIR, but the disordered chains differed in conformation from the well ordered material as previously shown by NMR (5,13). Mostly the disordered chains retained the O3H-O5' hydrogen bond that ensures chain rigidity, as shown by the hydroxyl stretching region in FTIR, but they had a dynamic mixture of all three possible conformations at C-6.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…Almost all the cellulose chains were at least moderately well oriented, as shown by both WAXS and polarized FTIR, but the disordered chains differed in conformation from the well ordered material as previously shown by NMR (5,13). Mostly the disordered chains retained the O3H-O5' hydrogen bond that ensures chain rigidity, as shown by the hydroxyl stretching region in FTIR, but they had a dynamic mixture of all three possible conformations at C-6.…”
Section: Discussionmentioning
confidence: 53%
“…S3). However for water-saturated spruce cellulose the observed column lengths were 2.9 nm normal to the (200) plane and a mean of 2.6 nm normal to the (110) and (1)(2)(3)(4)(5)(6)(7)(8)(9)(10) planes. In the dry state the 200 Scherrer dimension increased to 3.3 nm, probably due to either coalescence of partially detached chains or some degree of crystallographic stacking of adjacent microfibrils over short lengths where the 200 planes were aligned.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Eventually, in the early 1980s, the spectroscopic technique of solid-state 13 C cross-polarization magic-angle spinning NMR spectroscopy was able to resolve this issue by showing that native cellulose I diffraction data from many natural sources were a composite of diffraction from the two crystalline allomorphs Ia (triclinic unit cell) and Ib (monoclinic unit cell; Atalla and VanderHart, 1984). 13 C-NMR spectroscopy would not only confirm that the crystalline structure of the cellulose microfibril in most plants was a composite of Ia and Ib crystalline forms (Viëtor et al, 2002) but, in combination with Fourier transform IR spectroscopy spectra, suggested that the more crystalline inner chains of the microfibril core are composed primarily of cellulose Ib, while both forms of cellulose compose the chains in the surrounding paracrystalline sheath (Sturcová et al, 2004).…”
mentioning
confidence: 99%